2015
DOI: 10.1016/j.cell.2014.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Culture of Genome-Stable Bipotent Stem Cells from Adult Human Liver

Abstract: SummaryDespite the enormous replication potential of the human liver, there are currently no culture systems available that sustain hepatocyte replication and/or function in vitro. We have shown previously that single mouse Lgr5+ liver stem cells can be expanded as epithelial organoids in vitro and can be differentiated into functional hepatocytes in vitro and in vivo. We now describe conditions allowing long-term expansion of adult bile duct-derived bipotent progenitor cells from human liver. The expanded cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
1,654
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,275 publications
(1,790 citation statements)
references
References 61 publications
45
1,654
1
5
Order By: Relevance
“…Unlike LGR5, EpCAM, β-catenin, and GS were strongly expressed in ductular reactions as well as peri-septal hepatocytes, suggesting a role for LGR5 as a hepatocytespecific regeneration marker. This would be consistent with previous reports, which identified LGR5+ cells as only a small subset of EpCAM+ biliary cells isolated from adult and fetal human liver; although, the isolated cells themselves may not be comparable to those found in pediatric liver diseases (25,26). Since some LGR5 staining is still observed in biliary cells, these regions may represent a zone of transition, where both peri-septal hepatocytes and cholangiocytes take on a progenitor cell phenotype, possibly due to transdifferentiation of proliferating bile ducts into early hepatocytes at the interface (10,22,27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike LGR5, EpCAM, β-catenin, and GS were strongly expressed in ductular reactions as well as peri-septal hepatocytes, suggesting a role for LGR5 as a hepatocytespecific regeneration marker. This would be consistent with previous reports, which identified LGR5+ cells as only a small subset of EpCAM+ biliary cells isolated from adult and fetal human liver; although, the isolated cells themselves may not be comparable to those found in pediatric liver diseases (25,26). Since some LGR5 staining is still observed in biliary cells, these regions may represent a zone of transition, where both peri-septal hepatocytes and cholangiocytes take on a progenitor cell phenotype, possibly due to transdifferentiation of proliferating bile ducts into early hepatocytes at the interface (10,22,27).…”
Section: Discussionsupporting
confidence: 91%
“…Due to the diffuse parenchymal OV6 staining and lack of OV6 expression in normal human controls, the authors concluded that CK19-/ HEA125-/OV6+ hepatocytes could represent a less differentiated "progenitor stem cell-like phenotype," consisting of newly regenerated or transitional hepatocytes. More recently, Huch et al demonstrated that EpCAM+ cells could be isolated from the bile ducts of adult patients with A1ATD, expanded in long-term organoid cultures, and differentiated for in vitro disease modeling (25). These bipotent EpCAM+ sorted HPCs readily expressed the stem cell markers LGR5 and PROM1/CD133 in some but not all cells, as well as biliary a role for endogenous HPCs induced in human liver regeneration, and once again support the principle of immunophenotypic heterogeneity of HPCs depending on disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of a complex organ like the liver cannot be understood by analysis of a single type of cell, nor can the pathogenesis of genetic diseases affecting liver development be fully modeled using individual cells. Liver organoids have recently been produced from progenitor cells obtained from human liver tissue (31). However, human liver tissue is difficult to obtain and is available in very limited quantities.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, iPSCs were first dissociated into single cells and induced to form endoderm spheres in response to growth factors and chemicals added to the culture according to a modified protocol (30). The endodermal spheres then formed posterior foregut-like structures when cultured in the presence of a low concentration (1%-2%) of a Matrigel scaffold that supports the formation of 3D structures from stem cells (31,32), and by addition of various concentrations of FGF10, which is known to promote the differentiation of foregut endoderm into hepatic and gallbladder cells during organogenesis (33). The developing foregut structures were transferred on day 9 into a medium with other growth factors to promote their maturation into HOs.…”
Section: Generation Of Human Hepatic Organoids From Ipscsmentioning
confidence: 99%
“…This landmark paper established a novel experimental paradigm for generating tissue organoids. Subsequent studies worldwide confirmed the generalizability of such approach to human stem cells, and produced organoids of a variety of organ types including colon,11 intestine,12 prostate,13, 14 fallopian tube,15 stomach,16 liver,17, 18 kidney,19 lung,20 and brain 8…”
Section: Organogenesis In a Dish: An Overviewmentioning
confidence: 92%